2000
DOI: 10.1016/s0006-3495(00)76511-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics of Solid-State Lysozyme as Affected by Glycerol and Water: A Neutron Scattering Study

Abstract: Glycerol has been shown to lower the heat denaturation temperature (T(m)) of dehydrated lysozyme while elevating the T(m) of hydrated lysozyme (. J. Pharm. Sci. 84:707-712). Here, we report an in situ elastic neutron scattering study of the effect of glycerol and hydration on the internal dynamics of lysozyme powder. Anharmonic motions associated with structural relaxation processes were not detected for dehydrated lysozyme in the temperature range of 40 to 450K. Dehydrated lysozyme was found to have the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
161
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(189 citation statements)
references
References 36 publications
25
161
2
1
Order By: Relevance
“…At 220-230 K, the hydration water experiences a dynamical transition [20][21][22][23] that further increases anharmonicity. Finally, the onset of long-range translational motions of hydration water leads to an even faster increase in anharmonicity at temperatures above 240 K [47][48][49]. Thus, several different phenomena could contribute to the experimentally observed increase in the mean-squared displacements.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…At 220-230 K, the hydration water experiences a dynamical transition [20][21][22][23] that further increases anharmonicity. Finally, the onset of long-range translational motions of hydration water leads to an even faster increase in anharmonicity at temperatures above 240 K [47][48][49]. Thus, several different phenomena could contribute to the experimentally observed increase in the mean-squared displacements.…”
Section: Resultsmentioning
confidence: 95%
“…However, the exact mechanism of such "enslavement" has been extensively debated. For example, it has been reported that the transition is coupled to the onset of translational motions in hydration water [47][48][49]. In addition, it has been debated whether the transition is a real phenomenon, or merely a manifestation of the fact that the measurable atomic dynamics enter the experimentally accessible resolution window above certain temperatures [17,18,24,25,27].…”
Section: Resultsmentioning
confidence: 99%
“…To reach that value, a concentration of 40% w/w was needed for sucrose and 54% w/w for glycerol (see glycerol: MW 92), but both have been argued to be highly preferably excluded from the protein surface. [46][47][48] Nevertheless, Fig. 7 shows that glycerol significantly slows the relaxation kinetics in comparison with sucrose.…”
Section: Viscogen Dependencementioning
confidence: 91%
“…The term 'slaving' has been used to express that water can impose its dynamical fingerprint on a protein 11,12 . Cryo-temperature dependent neutron scattering experiments revealed the solvent dependence of dynamical transitions in soluble proteins [13][14][15][16][17][18][19][20][21] and in RNA 22 and provided insights into the coupling between them. Molecular dynamics simulations suggested the onset of water translational diffusion to be at the origin of the dynamical transition 23,24 .…”
Section: Introductionmentioning
confidence: 99%